A P300-Based Brain-Computer Interface for Improving Attention - Arvaneh, Mahnaz; Robertson, Ian H.; Ward, Tomas E. (Frontiers in Human Neuroscience, 2019)
A Brain-computer Interface (BCI) can be used as a neurofeedback training tool to improve cognitive performance. BCIs aim to improve the effectiveness and efficiency of the conventional neurofeedback methods by focusing on the self- regulation of individualised neuromarkers rather than generic ones in a graph- ically appealing training environment. In this work, for the first time, we have modified a widely used P300-based speller BCI and used it as an engaging neu- rofeedack training game to enhance P300. According to the user’s performance the game becomes more difficult in an adaptive manner, requiring the genera- tion of a larger and stronger P300 (i.e. in terms of total energy) in response to target stimuli. Since the P300 is generated naturally without conscious effort in response to a target trial, unlike many rhythm-based neurofeedback tools, the ability to control the proposed P300-based neurofeedback training is obtained after a short calibration without undergoing tedious trial and error sessions. The performance of the proposed neurofeedback training was evaluated over a short time scale (approximately 30 minutes training) using 28 young adult par- ticipants who were randomly assigned to either the experimental group or the control group. In summary, our results show that the proposed P300-based BCI neurofeedback training yielded a significant enhancement in the ERP compo- nents of the target trials (i.e. 150 ms to 550 ms after the onset of stimuli which includes P300) as well as attenuation in the corresponding ERP components of the non-target trials. In addition, more centro-parietal alpha suppression was observed in the experimental group during the neurofeedback training as well as a post-training spatial attention task. Interestingly, a significant improvement in the response time of a spatial attention task performed immediately after the neurofeedback training was observed in the experimental group. This paper, as a proof-of-concept study, suggests that the proposed neurofeedback training tool is a promising tool for improving attention particularly for those who are at risk of attention deficiency.